‘Once a finger is pointed at you, that part of you has gone’: The completion of Horizon programme in the community and carceral citizenship for men with sexual convictions - Fowler, Andrew (Probation journal, 2024)
This study presents an analysis of the experiences of 15 men convicted of sexual offences, from England and Wales, who have completed the Horizon treatment programme in the community, facilitated by The Probation Service. We found that whilst men felt initially coerced into the programme, finishing the programme was experienced as a significant loss of support. Beyond the programme, the men described the constraints on their citizenship, difficulty accessing support, and rejection in society due to their offence. We conclude by discussing the limitations of personal rehabilitation, the need for social rehabilitation, including tailored support beyond the programme, the importance of user voice and a ‘community integration paradox’.